ADAB EDUCATION IN POLYGAMOUS HOUSEHOLDS - Rico Setyo Nugroho (International Conference on Humanity Education and Society (ICHES), 2023)
Polygamy is one of the practices that Allah SWT prescribes for humans, but this practice in practice has a number of controversies unlike other practices, it has been proven that there are many failures in polygamous households, one of which is caused by a lack of adab education in polygamy. This type of research is qualitative research that takes references from various sources in the literature and is also included in field research. The purpose of this research is to describe the importance of polygamous etiquette education as a guide so that the failure of polygamous households can be minimized. The results of this study are that more and more people know about the etiquette of polygamy, it will make polygamous households civilized and avoid tyranny.